Perancangan Game Edukasi Kuis Lingkungan Menggunakan Metode Multimedia Development Life Cycle Dan Algoritma Fisher Yates Shuffle Pada Pengacakan Soal - Widi Aulia Widi (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2020)
Knowledge of nature or the environment is very important in life. Learning of this knowledge is also needed so that students know anything that can happen in this world, especially the current technological developments of science and knowledge can be easily provided through various media, one of which is a game that is widely developed and desired by the public. In its use, games can be used as a medium of learning at school so that learning activities can become more interesting and enjoyable. Another goal of this research is for students to know and care more about nature or the environment. The design and construction of this game uses the method of Multimedia Development Life Cycle (MDLC). This environmental quiz game is a learning medium that contains natural science lessons about living organization systems, the interaction of living things with the environment and environmental pollution. Components in this game are in the form of material and quiz and puzzle games. Quiz questions given will be randomized using the Fisher Yates Shuffle algorithm so that the position of the questions that come out is not the same. Keywords: Quiz game, Multimedia Development Life Cycle, Natural Knowledge, Shuffle, Fisher Yates Shuffle.